Poverty and Income Inequality: An International Comparison, 1980s and 1990s - Yaser Awad; Nirit Israeli (Luxembourg Income Study (LIS), 1997)
During recent years, both policy makers and administrators have become increasingly attentive to the economic distress of the weaker segments of society. In light of this development, many studies, including a number of comparative studies, were conducted both in Israel and throughout the world, for the purpose of measuring poverty incidence and income gaps while examining alternative ways for their reduction. This paper briefly reviews approaches to the measurement of poverty and the equivalence scales employed for the measurement of poverty by Israel, by LIS and by OECD member states. These scales differ in their estimation of the additional income required to compensate a household for the increase in its size and, thereby, maintain its standard of living. The second part of this paper presents the findings of the study.
Keywords: 330; Armut; Regionale Einkommensverteilung; Welt